Dictionary Ecology / Michael Allaby - Allaby, Michael (1998)
The updated second edition of the Dictionary of Ecology is the most comprehensive and authoritative dictionary of ecology available. Written in a clear, accessible style, it contains more than 6,000 entries on all aspects of ecology and related environmental scientific disciplines such as biogeography, genetics, soil science, geomorphology, atmospheric science, and oceanography